Delivering culturally adapted family interventions for people with schizophrenia in Indonesia: A feasibility randomised controlled trial and nested process evaluation - Laoise Renwick; Helen Brooks; Budi-anna Keliat; Dewi Wulandari; Rizqy Fadilah; Raphita Diorarta; Suherman; Georgia Addison; Penny Bee; Karina Lovell; Herni Susanti (PLoS ONE, 2026)
Schizophrenia is a severe and enduring illness with high relapse rates leading to functional impairment. Although family interventions effectively reduce relapse, most evidence originates from high-income settings. This single-masked feasibility trial randomised 74 service-user–carer dyads to receive either a culturally adapted family intervention or treatment as usual. The intervention was delivered by non-specialist healthcare workers through a task-shifting approach integrated into primary care. Feasibility outcomes indicated high recruitment and retention rates, strong intervention fidelity, and good acceptability among participants and facilitators. The process evaluation identified practical enablers and barriers to delivery and confirmed the feasibility of training and supervising non-specialist workers to implement the intervention. Findings provide confidence in progressing to a definitive trial based on the feasibility of recruiting participants and therapists and obtaining outcome measures at end point. Findings indicated there is potential for scaling culturally adapted family interventions within primary healthcare systems in low-resource settings. Further research should focus on refining measurements to ensure consistency and validity in trial methods, and explore factors related to therapist and implementation contexts to understand core and peripheral elements of culturally adapted interventions to optimise effectiveness and understand factors linked with implementation, policy and affordability benefits of improving access to mental healthcare.